A study on impact of specific nutritional and psycho-therapeutic interventions on performances on young soccer players - Chowdhury, N.; Ghosh, M.; Biswas, R.; Chattopadhaya, P.; Saha, S.; Dutta, S.; Ray, P. (Australian Conference of Science and Medicine in Sport and Third National Sports Injury Prevention Conference: 2003. Tackling the barriers of performance and participation, 2003)
To assess the impact of specific nutritional and psychological interventions on the physical fitness, motor performances and sports skills of young sports-persons, a community based controlled intervention study was undertaken. A sample of 65 adolescent (10 - 14 years; mean age 11.9 yrs.) male, residential trainee footballers were selected and exposed to uniform training in soccer .The subjects were grouped into five groups. Random allocation to different pre-designed Nutritional intervention schedules of gradually increasing high-carbohydrate, high-protein, and high fat and balanced diet regimes were done for continuous 17 wks, except in control group. The existing diet was modified and supplemented as required. Half of the subjects in each group also received specific psychotherapeutic interventions comprised of self-regulation technique and bio-feed back. Pre and post-intervention assessments of performance level were done through field tests, along with selected laboratory parameters. Balanced diet had little positive impact on sports performances, while protein-rich diet deteriorated both Work power and Athletic power. Fat-rich diet in late phase, significantly (p<0.05) improved Motor performance and Sports skill, but deteriorated (p<0.05) the Speed of movement. Carbohydrate-rich diet scored the top with significant improvements in Pulse-rate and C-R Endurance, Agility and Skill parameters. No significant blood or other biochemical changes was observed. Psychotherapeutic interventions caused positive impact on two Sports skill and two Motor performances whereas negative impact in Reaction time. The present study highlights the necessity of further studies for prolonged duration and on adequate sample size, in multiple centres with need-based, sports-discipline wise hypothesis developed from the present study.